Trauma and Mental Health in Resettled Refugees: Mediating Effect of Host Language Acquisition on Posttraumatic Stress Disorder, Depressive and Anxiety Symptoms. (February 2019) - Kartal, Dzenana; Alkemade, Nathan; Kiropoulos, Litza
This study examined the relationship between traumatic exposure, host language acquisition and mental health (posttraumatic stress, depressive and anxiety symptoms) in long-term resettled refugees. Participants included a community sample of Bosnian refugees ( N = 138, 55% male, mean age of 40 years old) that had resettled in Australia and Austria on average 18 years prior. Two mediation models were tested based on two competing theories. Model A examined whether language acquisition mediates the relationship between traumatic exposure and mental health problems experienced by refugees. Model B examined whether mental health symptoms mediate the relationship between exposure to traumatic events and the acquisition of host language. Model A fit the data well (CFI = 1.00, SRMR = .017, RMSEA < .001, χ 2 p = .526), while Model B was rejected as an acceptable model for the data (CFI = .556, SRMR = .136, RMSEA = .352). In Model A, the indirect pathway from trauma to mental health via language acquisition was significant for PTSD ( β = .067, p = .028) and anxiety symptoms ( β = .063, p = .026) but not depression symptoms ( β = .048, p = .071). Intervention strategies aimed at improving host language acquisition may be important not only in successful adaptation to daily living in the host country, but also to improve the mental health of traumatized refugees.